Neuronal Differentiation of Adipose Derived Stem Cells: Progress So Far - T. J. Moore; Heidi Abrahamse (International Journal of Photoenergy)
The nervous system is essential for normal physiological function of all systems within the human body. Unfortunately the nervous system has a limited capacity for self-repair and there are a plethora of disorders, diseases, and types of trauma that affect the central and peripheral nervous systems; however, current treatment modalities are unable to remedy them. Stem cell therapy using easily accessible mesenchymal stem cells, such as those found in the adipose stroma, has come to the fore in a number of biomedical disciplines as a potential therapeutic regime. In addition to substantial research already having been conducted on the in vitro differentiation of stem cells for the treatment of neurological repair, numerous strategies for the induction and culture of stem cells into terminal neural lineages have also been developed. However, none of these strategies have yet been able to produce a fully functional descendent suitable for use in stem cell therapy. Due to the positive effects that low level laser irradiation has shown in stem cell studies to date, we propose that it could enhance the processes involved in the differentiation of adipose derived stem cells into neuronal lineages.